PT Bank Panin Dubai Sharia: Profitability and the Factors Affect it - Meilinda, Aulia Sofia; SS, Vietha Devia (Review of Islamic Economics and Finance, 2023)
This study aims to examine the development of PT. Bank Panin Dubai Syariah. PT Bank Panin Dubai Syariah, also known as Bank Panin Syariah, is a sharia bank based in Jakarta, Indonesia. Founded in 1971 and is the first bank in Indonesia to introduce Islamic banking, especially the Bank that conducted its first IPO on the Indonesian stock exchange, precisely on January 15, 2014 with the code PNBS (Annual Report PNBS, 2020) and has a capital composition of 39.32%. from Dubai Islamic Bank. The author wants to examine the effect of interest rates, third party funds and financing on the profitability of Bank Panin Dubai Syariah. The author took the research period January 2020 - August 2022 because he wanted to see developments in bank profitability during the Covid-19 period. The data analysis tool used is a quantitative method with multiple linear regression analysis. The results showed that interest rates had no significant effect on the profitability of Bank Panin Dubai Syariah, while third party funds and financing had a significant positive effect on the profitability of Bank Panin Dubai Syariah. The implications of this research are expected to be used as an evaluation for banking institutions in managing interest rates, third party funds and financing which will affect bank profitability.